Simulation of bonding effects in HRTEM images of light element materials - Kurasch, Simon; Meyer, Jannik C.; Künzel, Daniela; Groß, Axel; Kaiser, Ute (Beilstein Journal of Nanotechnology, 2011)
The accuracy of multislice high-resolution transmission electron microscopy (HRTEM) simulation can be improved by calculating the scattering potential using density functional theory (DFT) . This approach accounts for the fact that electrons in the specimen are redistributed according to their local chemical environment. This influences the scattering process and alters the absolute and relative contrast in the final image. For light element materials with well defined geometry, such as graphene and hexagonal boron nitride monolayers, the DFT based simulation scheme turned out to be necessary to prevent misinterpretation of weak signals, such as the identification of nitrogen substitutions in a graphene network. Furthermore, this implies that the HRTEM image does not only contain structural information (atom positions and atomic numbers). Instead, information on the electron charge distribution can be gained in addition.In order to produce meaningful results, the new input parameters need to be chosen carefully. Here we present details of the simulation process and discuss the influence of the main parameters on the final result. Furthermore we apply the simulation scheme to three model systems: A single atom boron and a single atom oxygen substitution in graphene and an oxygen adatom on graphene.
Keywords: chemical bonding; DFT; graphene; HRTEM

(untitled) - Gemming, T.; Möbus, G.; Exner, M.; Ernst, F.; Rühle, M. (J. Microsc., 1998)

(untitled) - Deng, B.; Marks, L. D. (Acta Crystallogr., Sect. A, 2006)

Advanced Computing in Electron Microscopy - Kirkland, E. J. (Plenum Press, 1998)

(untitled) - Hébert, C. (Micron, 2007)

(untitled) - Rose, H. (Optik, 1990)

(untitled) - Haider, M.; Rose, H.; Uhlemann, S.; Kabius, B.; Urban, K. J. (Electron Microsc., 1998)

(untitled) - Deng, B.; Marks, L. D.; Rondinelli, J. M. (Ultramicroscopy, 2007)

(untitled) - Zhu, Y.; Wu, L.; Tafto, J. (Microsc. Microanal., 2003)

(untitled) - Zuo, J. M.; Spence, J. C. H.; O’Keeffe, M. (Phys. Rev. Lett., 1988)

(untitled) - Ciston, J.; Kim, J.; Haigh, S.; Kirkland, A.; Marks, L. (Ultramicroscopy, 2010)

(untitled) - Meyer, J. C.; Chuvilin, A.; Algara-Siller, G.; Biskupek, J.; Kaiser, U. (Nano Lett., 2009)

(untitled) - Meyer, J. C.; Kurasch, S.; Park, H. J.; Skakalova, V.; Künzel, D.; Groß, A.; Chuvilin, A.; Algara-Siller, G.; Roth, S.; Iwasaki, T.; Starke, U.; Smet, J. H.; et al. (Nat. Mater., 2011)

(untitled) - O’Keefe, M. A. (Ultramicroscopy, 1992)

(untitled) - Thust, A. (Phys. Rev. Lett., 2009)

(untitled) - Lehmann, M.; Lichte, H. (Microsc. Microanal., 2002)

(untitled) - Doyle, P. A.; Turner, P. S. (Acta Crystallogr., Sect. A, 1968)

(untitled) - Coulthard, M. A. (Proc. Phys. Soc., London, 1967)

(untitled) - Kresse, G.; Furthmüller, J. (Phys. Rev. B, 1996)

An Augmented Plane Wave + Local Orbitals Program for Calculating Crystal Properties - Blaha, P.; Schwarz, K.; Madsen, G. K. H.; Kvasnicka, D.; Luitz, J. (WIEN2k; Karlheinz Schwarz, Techn. Universitat Wien, 2001)

wien2venus.py - Arai, M.

Density Functional Theory, the family of (L)APW-methods: a step-by-step introduction - Cottenier, S. (Instituut voor Kern- en Stralingsfysica, K. U. Leuven, 2002)

(untitled) - Perdew, J.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Schowalter, M.; Lamoen, D.; Rosenauer, A.; Kruse, P.; Gerthsen, D. (Appl. Phys. Lett., 2004)

(untitled) - Hÿtch, M. J.; Stobbs, W. M. (Ultramicroscopy, 1994)

(untitled) - Gómez-Navarro, C.; Meyer, J. C.; Sundaram, R. S.; Chuvilin, A.; Kurasch, S.; Burghard, M.; Kern, K.; Kaiser, U. (Nano Lett., 2010)

(untitled) - Yan, J.-A.; Chou, M. Y. (Phys. Rev. B, 2010)